Studies on the removal of nickel from aqueous solutions using modified riverbed sand - Yadav S.; Srivastava V.; Banerjee S.; Gode F.; Sharma Y.C. (My University, 2025)
This paper highlights the utility of riverbed sand (RS) for the treatment of Ni(II) from aqueous solutions. For enhancement of removal efficiency, RS was modified by simple methods. Raw and modified sands were characterized by scanning electron microscope (SEM), Energy Dispersive Spectroscopy (EDS), and Fourier Transform Infrared Spectroscopy (FTIR) to investigate the effect of modifying the surface of RS. For optimization of various important process parameters, batch mode experiments were conducted by choosing specific parameters such as pH (4. 0-8. 0), adsorbent dose (1. 0-2. 0 g), and metal ion concentrations (5-15 mg/L). Removal efficiency decreased from 68. 76 to 54. 09 % by increasing the concentration of Ni(II) in solution from 5 to 15 mg/L. Removal was found to be highly dependent on pH of aqueous solutions and maximum removal was achieved at pH 8. 0. The process of removal follows first-order kinetics, and the value of rate constant was found to be 0. 048 min-1 at 5 mg/L and 25 °C. Value of intraparticle diffusion rate constant (kid) was found to be 0. 021 mg/g min1/2 at 25 °C. Removal of Ni(II) decreased by increasing temperature which confirms exothermic nature of this system. For equilibrium studies, adsorption data was analyzed by Freundlich and Langmuir models. Thermodynamic studies for the present process were performed by determining the values of ΔG°, ΔH°, and ΔS°. Negative value of {increment}H° further confirms the exothermic nature of the removal process. The results of the present investigation indicate that modified riverbed sand (MRS) has high potential for the removal of Ni(II) from aqueous solutions, and resultant data can serve as baseline data for designing treatment plants at industrial scale. © 2012 Springer-Verlag.